The integration of maqasid sharia principles on digital accounting information system in Indonesian Islamic microfinance - Provita Wijayanti; Intan Salwani Mohamed; Dalila Daud; Hani Werdi Apriyanti; M. Ja’far Shodiq; Arifathul Khoiriyah (Universitas Islam Negeri Walisongo Semarang, 2025)
Purpose - This study analyzes the integration of Maqasid sharia Principles into the digital accounting information system (DAIS) in Indonesian Islamic Microfinance (BMTs). Method - This is a descriptive quantitative study with a survey method distributed to 226 of 455 key decision-makers across accredited BMTs, consisting of members of the Supervisory Board, Board of Committees, Managers, Heads of Operations/Finance, and Heads of Marketing. Result - This study found that integrating Maqasid sharia on DAIS is highly effective (84%). The highest scores were recorded for Hifdzul Maal (6.28), Hifdzul Aql (6.26), Hifdzul Diin (6.24), and Hifdzul Nasl (6.18), while Hifdzul Nafs (6.05) showed the lowest score. Implication - This study highlights the need for greater attention to the Hifdzul Nafs dimension by expanding access to microfinance for low-income communities and strengthening partnerships with other institutions. Policymakers and BMT management should integrate regular monitoring and evaluation to improve the effectiveness and offer valuable insights on financial inclusion and social welfare in Indonesia. Originality - This is the original study that firstly evaluates the integration across the five Maqasid sharia dimensions and provides a comprehensive assessment of its alignment with Islamic principles.